Pandangan Islam Tentang Kesehatan Dan Higenitas - ., Ika; ., Rohani; ., Sherly Ananda; ., Sifa Safitri (CV. ITTC INDONESIA, 2023)
The environment is a place for humans to live on earth, and the environment is something that cannot be separated from humans so that humans can naturally interact through their environment. A clean environment reflects the quality of life of a healthy community. Humans as caliphs on earth have an important role and obligation to protect and manage their environment properly, so as to create an environment that is clean, healthy, free from disease and free from natural disasters. In the teachings of Islam itself, cleanliness is mandatory and absolute. As the Prophet Muhammad always taught his people to always maintain cleanliness. However, keeping the environment clean is not as easy as imagined, there are still hands who are not responsible for the environment such as littering, even though keeping the environment clean only requires the awareness of all parties and layers of society to create a clean and comfortable environment. And in Islamic teachings about water, sanitation, cleanliness and environmental health, it turns out that all levels of society do not really know and understand it, so that infectious diseases often occur due to unclean water and poor sanitation. The Al-Qur'an and hadith are sources of Islamic teachings which clearly explain in them how humans should maintain health and environmental cleanliness. The hadiths studied are the hadiths contained in al-polar sittah. The method used in this research is normative empirical method. And to obtain data and information related to environmental hygiene and health, researchers used the library research method. In this case, it can be concluded that the concept of environmental hygiene and health in the hadith is the same as the concept of biocentrism environmental ethics, namely the theory that views every life and living creature as having value and worth so that humans have a moral obligation to the environment. Therefore, humans must always maintain the cleanliness of water sources, cleanliness of homes, cleanliness of public areas and not cut down trees and plants in public places without an unclear purpose.